Hazard Identification and Risk Assessment of Sensor Maintenance Work Activity on The Suramadu Bridge Steel Box Girder Area - Nabylla Sharfina Sekar Nurriwanti; Y. Denny A. Wahyudiono; Indriati Paskarini; Ayu Pertimasari Sekar Handayani (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: The steel box girder of Suramadu Bridge is a confined work area with sensor maintenance activities and potential hazards. The purpose of this study was to determine the potential hazards and risk levels in the Suramadu Bridge steel box girder work area. Methods: This descriptive study involved cross-sectional data collection. This study used a qualitative risk assessment method. The primary data used in this research included interviews with informants, which consisted of five key informants from experts and five main informants from technicians. The secondary data of the study include a job safety analysis document issued by the Suramadu Bridge Structural Health Monitoring System (SHMS). Risk assessment was performed by determining the level of likelihood and consequences using a risk analysis matrix. Data processing techniques and analysis are based on job safety analysis documents and interviews, whereas the risk analysis table is based on AS/NZS 4360 (2004). Results: The study results show that sensor maintenance work in the steel box girder area involves eight activities, 15 potential hazards, and 19 risks. Conclusion: The study concludes that, Out of the 19 identified risks, three risks (16%) were in the low-risk category, 15 risks (79%) were in the medium-risk category, and one risk (5 %) was in the high-risk category with the potential for fire.